Proposed new interior design of Intel Computer Clubhouse Network at Lot123, Jalan Maarof, Bangsar Park, 59000 Kuala Lumpur for Intel Malaysia / Siti Aishah Yusof - Yusof, Siti Aishah (Faculty of Architecture, Planning and Surveying, 2011)
The final project of interior design for final semester student is the representation of students’ understnding towards the process and important aspects of interior designing that has been studied analyzed from that very beginning of design. This is the report on project proposed new interior design scheme of Intel Computer Clubhouse Network (ICCN) at 123, Jalan Maarof, Bangsar Park, 59000 Kuala Lumpur for Intel Malaysia. The concept of youth clubhouse is still new to the society but it gives benefit to the community especially to the teen. This thesis is to acknowledge people about the development of designing an interactive clubhouse. The learning environment and socializing space must go hand-in-hand in order to meet the teenage needs and wants. It is a details study of flows and space with terms of youth physcology. All the data and details that been collected from research and observation conducted, was used as a parameter in the design process. Proper study of space and its flow made to have a better understand of the building function itself. All the design is visualize in sketches and drawing. The concept is to create a bold design for the interior to give it a dynamic character. The compilation of my work during the progress is the documentated in my report. It contains all the necessary information about my project. This thesis is hope to be a reference in the future in designing a youth clubhouse.